RELATION BETWEEN KNOWLEDGE OF TYPE 2 DIABETES PATIENTS WITH SOME PARAMETERS - Võ Duy , Ân; Trần Thanh, Mân; Nguyễn Văn, Chương; Nguyễn Ngọc, Châu (Journal of 175 Practical Medicine and Pharmacy, 2023)
Objective: To examine the relation between disease knowledge and some parameters features in patients with type 2 diabetes. Subjects and methods: A cross-sectional descriptive study was performed on 205 diabetes patients was treated in 175 Military Hospital was investigate the knowledge about disease by BDK includes 23 items. From January 2019 to April 2020. Results: The level of Diabetes Knowledge decreases with age, p<0,01. The ages ≤ 60 with knowledge better than ages ≥ 61, with OR=1.955, p<0.05. The patient’s diabetes knowledge has no significant with sex, duration of disease and degree of blood glucose control (HbA1c), p>0.05. However, the level of knowledge is related to jobs and education level, p <0.001. Conclusion: Patient’s diabetes knowledge has significant relation with age, education level and jobs.